Integration of Operations Management and Marketing Strategies at Agoda: A Case Study - Gusniar, Bella; Serenade, Vincensia; Nono, Yuprianingsi Fatmawati (Jurnal Informatika Ekonomi Bisnis, 2024)
This study delves into how Agoda, a prominent online travel platform, seamlessly integrates its operational and marketing strategies to thrive in the highly competitive travel industry. By analyzing Agoda's business model and strategic practices, the research uncovers how this synergy creates a significant competitive edge. Agoda's success is deeply rooted in its innovative use of technology, data analytics, and customer-focused approach. By harnessing data, Agoda personalizes recommendations and deals, enhancing customer satisfaction. The company also optimizes its operations through technology, boosting efficiency and cutting costs.Agoda's global expansion strategy is another key factor, as it adapts to local markets while maintaining a cohesive brand identity. This strategic harmony between operations and marketing allows Agoda to stay ahead in the rapidly changing global travel market. The findings of this research offer valuable lessons for other industry players, emphasizing the importance of data-driven decisions, tailored customer experiences, and a strong focus on customer needs. Agoda's journey provides an inspiring example of how integrating operations and marketing can lead to sustainable growth and competitiveness in a dynamic industry. This research contributes to the ongoing discussion about successful business strategies within the online travel sector, offering practical insights for companies aiming to enhance their market position.